Application of the Fuzzy Mamdani Method to Predict the Number of Customers Based on the Weather and Holidays in a Simple Restaurant on Abdul Hakim Street - Gultom, Parapat; Thianujaya, Wendy Thianujaya; Sirait, Annisa Hidayati; Kristian, Abel (Talenta Publisher, 2024)
This research aims to optimize marketing strategies in the food industry byapplying the Fuzzy Mamdani method. This approach considers factors such as thenumber of customers, weather conditions, and holidays to forecast the number ofcustomers who will come to a simple restaurant. By using the Fuzzy Mamdanimodel, this research seeks to generate more effective marketing strategies bytaking into account variability in consumer behavior. The results of this researchare expected to help food business owners to optimize their raw material inventorymore precisely, so as to improve operational efficiency and increase customersatisfaction.